Innovations in earthquake risk reduction for resilience: Recent advances and challenges. (15th June 2021) - Freddi, Fabio; Galasso, Carmine; Cremen, Gemma; Dall'Asta, Andrea; Di Sarno, Luigi; Giaralis, Agathoklis; Gutiérrez-Urzúa, Fernando; Málaga-Chuquitaype, Christian; Mitoulis, Stergios A.; Petrone, Crescenzo; Sextos, Anastasios; Sousa, Luis; et al.
Abstract: The Sendai Framework for Disaster Risk Reduction 2015–2030 (SFDRR) highlights the importance of scientific research, supporting the 'availability and application of science and technology to decision making' in disaster risk reduction (DRR). Science and technology can play a crucial role in the world's ability to reduce casualties, physical damage, and interruption to critical infrastructure due to natural hazards and their complex interactions. The SFDRR encourages better access to technological innovations combined with increased DRR investments in developing cost-effective approaches and tackling global challenges. To this aim, it is essential to link multi- and interdisciplinary research and technological innovations with policy and engineering/DRR practice. To share knowledge and promote discussion on recent advances, challenges, and future directions on 'Innovations in Earthquake Risk Reduction for Resilience', a group of experts from academia and industry met in London, UK, in July 2019. The workshop focused on both cutting-edge 'soft' ( e.g., novel modelling methods/frameworks, early warning systems, disaster financing and parametric insurance) and 'hard' ( e.g., novel structural systems/devices for new structures and retrofitting of existing structures, sensors) risk-reduction strategies for the enhancement of structural and infrastructural earthquake safety and resilience. The workshop highlighted emerging trends and lessons from recent earthquake events and pinpointed critical issues for future research and policy interventions. This paper summarises some of the key aspects identified and discussed during the workshop to inform other researchers worldwide and extend the conversation to a broader audience, with the ultimate aim of driving change in how seismic risk is quantified and mitigated.